Ca2+ signaling alterations in Alzheimer's disease - Stutzmann, Grace (Henry Stewart Talks, 2012)
Neuronal Ca2+ signaling pathways and associated functions/dysfunctions, Alzheimer's disease, features and mechanisms, Alzheimer's disease and calcium signaling deficits, sources, specific effects on synaptic transmission, early and late contributions to pathology, How dysregulated calcium can feed into AD pathology